Tissue-Specific Requirement for the GINS Complex During Zebrafish Development - Varga, Máté; Csályi, Kitti; Bertyák, István; Menyhárd, Dóra K.; Poole, Richard J.; Cerveny, Kara L.; Kövesdi, Dorottya; Barátki, Balázs; Rouse, Hannah; Vad, Zsuzsa; Hawkins, Thomas A.; Stickney, Heather L.; et al. (Frontiers in Cell and Developmental Biology, 2020)
Efficient and accurate DNA replication is particularly critical in stem and progenitor cells for successful proliferation and survival. The replisome, an amalgam of protein complexes, is responsible for binding potential origins of replication, unwinding the double helix, and then synthesizing complimentary strands of DNA. According to current models, the initial steps of DNA unwinding and opening are facilitated by the CMG complex, which is composed of a GINS heterotetramer that connects Cdc45 with the mini-chromosome maintenance (Mcm) helicase. In this work, we provide evidence that in the absence of GINS function DNA replication is cell autonomously impaired, and we also show that gins1 and gins2 mutants exhibit elevated levels of apoptosis restricted to actively proliferating regions of the central nervous system (CNS). Intriguingly, our results also suggest that the rapid cell cycles during early embryonic development in zebrafish may not require the function of the canonical GINS complex as neither zygotic Gins1 nor Gins2 isoforms seem to be present during these stages.